Peripheral Nerve Protection Strategies: Recent Advances and Potential Clinical Applications - Weronika Radecka; Wiktoria Nogalska; Maria Siemionow (Journal of Functional Biomaterials)
Peripheral nerve injuries (PNIs) are a significant clinical challenge, often resulting in persistent sensory and motor deficits despite surgical repair. Autologous nerve grafts remain the gold standard for repair; however, outcomes are frequently suboptimal due to donor site morbidity and inconsistent functional recovery. A major obstacle in nerve regeneration is the formation of postoperative adhesions and fibrosis, which impede healing and necessitate revision surgeries. Nerve protectors from biological, synthetic, and hybrid materials offer a promising tissue engineering strategy to enhance nerve regeneration. These protectors are applied as a protective barrier when a nerve is severed without the gap, allowing for direct repair. They provide mechanical support and reduce scarring. Biocompatible biological wraps, including vascularized fat flaps, vein wraps, collagen-based materials, human amniotic membrane (hAM), porcine small intestinal submucosa (PSIS), and chitosan, modulate immune responses and promote vascularization. Synthetic alternatives, like polycaprolactone (PCL), provide mechanical stability with controlled degradation. Hybrid wraps, such as PCL-amnion, combine the benefits of both. Despite optimistic results, the heterogeneity of study methodologies hinders direct comparisons and standardization. This review highlights the latest developments in nerve wraps, their clinical applications, limitations, and future potential, guiding clinicians in selecting the most appropriate materials for peripheral nerve repair.